Improving Problem Solving Ability through A Scientific Approach on Grade VII MTs Students - Iman, Pathiah Fikri; Fitriani, Nelly ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Problem-solving skills are highly important in various aspects of life and professions, particularly in mathematics education. However, many students struggle to develop these skills due to a lack of understanding, critical thinking abilities, practice, and motivation. To address this, educators need to adopt teaching strategies that strengthen students' problem-solving skills. One effective approach is the scientific learning model, which emphasizes the scientific process, critical thinking, collaboration, and real-world applications. This study aims to assess the improvement of seventh-grade students' mathematical problem-solving skills using the scientific learning model. The research utilizes a descriptive quantitative approach with a two-group pretest-posttest design. The sample consists of seventh-grade students from an Islamic Junior High School, and data collection includes pretest and posttest questions. The N-gain formula is used to measure improvement. The findings indicate a significant improvement in problem-solving abilities among students who receive instruction using the scientific learning model compared to those who do not. The improvement is categorized as moderate in the experimental class, while the control class shows a lower level of improvement. Factors such as students' enthusiasm, implementation of real-life problems, and increased independence contribute to the improvement in students' problem-solving abilities. The implementation of the scientific learning model significantly enhances students' mathematical problem-solving skills. Based on the field findings, there is a need for improvement in soft skills to support meaningful learning activities.